Challenges of People Management in MEMOS Software - Zwinger, Michal (2011)
Organically growing companies usually reach a point when people management starts to be challenging up to such scale that influences their further development. This master thesis in its first part covers basic topics essential for people management, especially communication, work motivation, job design and leadership. In the second part of this work is focus put on empiric research of a concrete situation inside the selected company, analyses of management interviews and employee questionnaires. The last part then presents a set of recommendations adjusted directly for the researched company in order to help improve current situation.